Social Conflicts Between Oil-Palm Plantation Company and Indigenous People in Jambi Province - Nilakrisna, Dewi; Taqwa, Ridha; Sriati, Sriati; Purnama, Dadang Hikmah; Susanto, Robiyanto Hendro (Journal of Tropical Life Science, 2016)
The oil-palm plantation development policy meant to increase the economic growth and to provide jobs opportu nities in rural area. The development policy that participate the private sectors creates many social conflict in Indonesia, especially against the indigenous people community. The purpose of this research is to fid out, how the oil-palm plantation development policies implemented and the impact to the indigenous people community in Batanghari Regency, Jambi Province. This qualitative research used case study approach and qualitative data anal ysis based on extended text. Obtaining data through direct observation, in-depth interview, structured interview, and literature studies.The study results showed that the implementation of the large scale oil-palm plantation development policy, has caused approximately 1/3 area of Batang Hari Regency was controlled by the private companies and give negative impacts to almost 3.000 peoples of SAD Batin 9 community. They have been evicted, marginalized and face the uncertainty rights to the land. The implementation of oil palm plantation development policy without take a no tice to the existing social environmental condition has deny the indigenous people existence. It has stimulated some contradiction to the injustice government policy. Therefore this research recommends the government to consider about the social and environmental impacts before issued any policy in order to protect the social justice for all citizens.